1997
DOI: 10.1017/s0022112096003990
|View full text |Cite
|
Sign up to set email alerts
|

Convection and flow in porous media. Part 1. Visualization by magnetic resonance imaging

Abstract: We describe an experimental study of porous media convection (PMC) from onset to 8Ra c . The goal of this work is to provide non-invasive imaging and high-precision heat transport measurements to test theories of convection in PMC. We obtain velocity information and visualize the convection patterns using magnetic resonance imaging (MRI). We study both ordered and disordered packings of mono-disperse spheres of diameter d = 3.204 ± 0.029 mm, in circular, rectangular, and hexagonal planforms. In general, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…The general solution of [6] satisfying the boundary conditions v ͑r ϭ R͒ ϭ 0 ͑at wall͒ [7] v ͑r ϭ 0͒ ϭ finite [8] is…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The general solution of [6] satisfying the boundary conditions v ͑r ϭ R͒ ϭ 0 ͑at wall͒ [7] v ͑r ϭ 0͒ ϭ finite [8] is…”
Section: Theorymentioning
confidence: 99%
“…25,26). Recently, MRI was used to visualize thermal convection in porous media (7) and in a flat horizontal layer (8).…”
Section: Introductionmentioning
confidence: 99%
“…The upper limit value of the Ra for Darcy's law practicable need to be explored in the laboratory. This is because the higher the Rayleigh number is pushed, the smaller the pore scales must be for the Darcy's law to remain valid [28]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent experimental study of natural convection in ordered and disordered porous media was investigated by Shattuck et al (1997), using magnetic resonance imaging to visualize the convection patterns. In general, it is found that the structure of the medium plays a role which is not predicted by theories which assume a homogeneous system.…”
Section: Introductionmentioning
confidence: 99%